The Use of Mentoring to Prepare Māori Tertiary Students for Employment - Katu, Melanie June Makareta (Auckland University of Technology, 2015)
The purpose of this research is to investigate how mentoring can prepare Māori tertiary students for employment. Representation of Māori in New Zealand business employment is low compared to non-Māori (Mintrom, 2005). Research has shown that mentoring can support both improved Māori student retention and achievement in tertiary education (Tahau-Hodges, 2010) as well as assist graduates to prepare for post-tertiary activity (Martin, Milne-Home, Barrett, & Jones, 2010). The Māori economy is flourishing within the New Zealand economy (Ministry of Business Innovation and Employment, 2015), and the New Zealand government is asking tertiary organisations to prepare their graduates for employment in these areas. This research explores mentoring relationships between four Māori tertiary students and four business mentors. The mentors are currently employed in the business area the Māori tertiary student wishes to enter once graduated. The Māori tertiary students are currently studying business qualifications with majors in human resources (HR), accounting, law and business finance. The study was managed through a series of hui (meetings) between the researcher and participants. The Māori approach of whānaungatanga (relationship through shared connections) was used in the first hui, to introduce the mentor to the mentee and establish the mentoring relationship. This facilitated meeting assisted participants to decide on what they would do together to prepare the Māori tertiary student for employment. In addition, manaakitanga (to nurture), kaupapa (collective vision) and ako (reciprocity of teaching and learning) underpinned the way in which the mentoring relationship was presented to participants; as a result, they were able to connect, collaborate and learn from each other as the mentoring relationship progressed. The findings showed that mentoring by an industry mentor assisted the Māori tertiary students to prepare for employment because they were able to learn about the wider business industry, job functions, employment opportunities, study advice, creating networks and cultural considerations. The use of mentoring to prepare Māori tertiary students for employment also created an opportunity for the students to explore the potential contribution they can make to the business world. This supports the view held by Buckley and Zimmerman (2003) where mentoring can promote positive identity as well as encourage employment ambitions. All mentors and mentees were satisfied about the knowledge they had gained as a result of mentoring and offered useful suggestions for future mentoring programmes. Therefore, this research study leaves the research community with insight and direction as to how mentoring can be used to prepare Māori tertiary students for employment.
Keywords: Mentoring; Maori; Indigenous; Tertiary; Employment